Survival after refractory cardiogenic shock is comparable in patients with Impella and veno-arterial extracorporeal membrane oxygenation when adjusted for SAVE score. Issue 4 (June 2019) - Schiller, Petter; Hellgren, Laila; Vikholm, Per
Objectives: Survival after different short-term mechanical circulatory support is difficult to compare because various systems are used and patient disease severity is most often not adjusted for. This study compares the outcome after the use of Impella and veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in refractory cardiogenic shock, adjusted for disease severity through the survival after the VA-ECMO (SAVE) score. Methods: Patients with refractory shock treated with either VA-ECMO or Impella between January 2003 and August 2015 were included. Data were analysed to assess short and long-term survival and complications. The SAVE score was calculated for the two groups and outcome was compared adjusted for the SAVE score. Results: There was no difference between VA-ECMO patients ( n =46) and Impella patients ( n =48) in mean age or renal failure. ECMO patients were more often intubated and had lower diastolic blood pressure at device implantation. ECMO patients had a lower SAVE score (–0.4 (6.5)) compared to Impella patients (4.1 (5.4)). There was no difference in intensive care unit survival between ECMO patients 65% (52–80) or Impella patients 63% (55–79), or long-term survival between groups. When stratified into worse (III–IV) or better SAVE class (I–II) there was no difference in survival between the groups. Conclusions: Short and long-term survival is not measurably different among patients treated with Impella or VA-ECMO due to refractory cardiogenic shock, after adjustment for disease severity through the SAVE score.